The merit and seniority ranking system in the Bureau of Public Schools - Tuy, Salvador M. 1918- ([Quezon City s.n.], 1961)
This investigation is a historical and analytical presentation of the merit system as it is adopted in the Bureau of Public Schools. A revision of the present merit and seniority ranking system is proposed and a more positive application of its criteria is recommended.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Teachers, Rating of